Defects in Cytoskeletal Signaling Pathways, Arrhythmia, and Sudden Cardiac Death - Smith, Sakima A.; Curran, Jerry; Hund, Thomas; Mohler, Peter J. (Frontiers in Physiology, 2012)
Ankyrin polypeptides are cellular adapter proteins that tether integral membrane proteins to the cytoskeleton in a host of human organs. Initially identified as integral components of the cytoskeleton in erythrocytes, a recent explosion in ankyrin research has demonstrated that these proteins play prominent roles in cytoskeletal signaling pathways and membrane protein trafficking/regulation in a variety of excitable and non-excitable cells including heart and brain. Importantly, ankyrin research has translated from bench to bedside with the discovery of human gene variants associated with ventricular arrhythmias that alter ankyrin–based pathways. Ankyrin polypeptides have also been found to play an instrumental role in various forms of sinus node disease and atrial fibrillation (AF). Mouse models of ankyrin-deficiency have played fundamental roles in the translation of ankyrin-based research to new clinical understanding of human sinus node disease, AF, and ventricular tachycardia.